Caregiver Burden and Quality of Life of Key Caregivers of Patients with Dementia - Srivastava, Garima (Indian J Psychol Med, 2016)
BACKGROUND: Dementia is the most devastating cognitive disorder of the elderly and needs extra attention to care. Therefore, this study was conducted to identify the caregiver burden of dementia key caregivers and their Quality of Life (QOL). MATERIALS AND METHODS: Sample consisted of purposively selected 24 dementia key caregivers fulfilling the inclusion criteria from the in-patient of the Department of Geriatric Mental Health, King George's Medical University, Lucknow, Uttar Pradesh, India. Zarit Burden Interview and World Health Organization QOL-BREF were administered. Mean, standard deviation, t-test, Chi-square with Yate's correction were used to analyze the data. RESULTS: All key caregivers felt mild to moderate level of burden. Gender-wise significant difference was found on burden area of expectation (P < 0.05). Mean scores on physical, psychological, social relationship, and environmental QOL were found to be on lower side. A negative correlation was found between burden and QOL. CONCLUSION: Professional help and supportive psychotherapy can be provided to the key caregivers of dementia patients to reduce their burden, strengthen the coping skill and thus improve their QOL.